PENGEMBANGAN MODUL BERBASIS CONTEXTUAL LEARNING PADA MATAKULIAH ZOOLOGI VERTEBRATA DI PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN ILMU PENDIDIDKAN UNIVERSITAS ISLAM RIAU - Laili Rahmi (Universitas Negeri Medan, 2018)
This study aims to determine and test the feasibility of a teaching materials module based on Contextual Learning in Vertebrate Zoology courses in the learning process in Biology Education Study Program Faculty of Teacher Training and Education University of Islam Riau Year 2015-2016. This research uses ADDIE model as research design consisting of five stages; Analysis, Design, Development, Implementation and Evaluation. But the research design only test on the feasibility of the module so that this research only through three stages of Analysis, Design, Development. The selection of subjects is determined from the total of students who take the Vertebrate Zoology course as many as 195 people then selected by Random Sampling of 45 people. This is because the subject and the subject character are the same. The instrument used in this study is a questionnaire. The results of the research show at the Analysis stage; there needs to be a more interesting learning innovation, so that students are more active in constructing their knowledge through more relevant learning resources. Next at Design stage; the requirements of the design stage are adjusted to the steps already described in the RPS (Semester Course Plan). At Development stage; the results of the validation of materials experts by 80% with the criteria module feasible to use, the material expert judgment of 82% with the criteria module feasible to use, and student ratings states the module appeals to students with 90% percentage (very worthy to use). So it can be concluded that the learning process associated with constructing the pemahan students is not only limited to the exposure of the material, but also reflects the activities and learning activities that must be done. so students can explore the source of learning by building their knowledge through direct interaction with the experience and environment.Keywords: Development Module, Contextual Learning, Vertebrate Zoology.